Adoption of mobile banking to promote financial inclusion among rural farming community: Drivers and satisfaction level perspective - Most Nilufa Khatun; Md Nazirul Islam Sarker; Sandip Mitra (Journal of Agriculture and Food Research)
This study investigates the factors driving mobile banking adoption and user satisfaction to enhance financial inclusion among rural farming communities, using survey data from 400 farmers. An unpaired t-test reveals a significant difference in receiving international remittance, fund transfers, mobile recharge, and allowance during and before COVID-19, but no significant difference in cash-in, cash-out, and utility bill payments. During the pandemic, most mobile banking transactions increased in volume and frequency. The result also reveals that the majority of rural people (approximately 88 %) enjoy mobile banking services. The Index value of farmers' satisfaction level towards mobile banking transactions indicates that respondents were satisfied with various mobile banking transactions but were dissatisfied with the higher service fees. Logit estimation shows that age, education, income, farm size, and distance from the bank branch were the primary factors driving the adoption of mobile banking among rural farming communities. However, expansion of agent service, reduction of service charges, and protection from fraudulent transactions are essential for expanding the adoption of mobile banking services in rural areas and accelerating their financial inclusion.